"You have to find a caring man, like your father!" gendering sickle cell and refashioning women's moral boundaries in Sierra Leone. (August 2020) - Berghs, M.; Dyson, S.M.; Gabba, A.; Nyandemo, S.E.; Roberts, G.; Deen, G.
Abstract: Most research on sickle cell disorders has tended to be gender-blind. This qualitative study undertaken in 2018, explores if and how sickle cell disorders become gendered in Sierra Leone through the analytical framework of a feminist ethics of care. It argues that women have to navigate moral blame when they have children with the condition. At the same time women refashion moral boundaries so that gendered norms around childhood and parenting for such children become suspended, in favour of creation of careful spaces. Parental fears of physical and sexual violence mean that gendered sexual norms are enforced for teenage boys as they are encouraged into early adulthood. In contrast, girls are kept in enforced ignorance about the consequences of sickle cell for reproduction and are encouraged to delay motherhood. This is because, as women relate, relationships and giving birth are fraught with embodied dangers and risks of violence. Highlights: Using a feminist ethics of care analysis, examines how sickle cell disorders become gendered. Professionals act as caring pioneers to stop mothers being blamed for children with the condition. As children, gendered norms for girls and boys are suspended in favour of careful spaces. Parental fears of effects of violence mean girls and boys socialised differently into adulthood. Policy neglect and male standard in practice leads to lack of reproductive justice and violence.